Enhancing Photovoltaic Efficiency through Paraffin–Pomegranate Phase Change Composites: An Experimental Approach with Bibliometric Analysis toward Sustainable Thermal Management Aligned with Sustainable Development Goals (SDGs) - Ali M. Jawarneh; Faris M. AL‑Oqla; Mohamad Otair (Bumi Publikasi Nusantara, 2026)
Overheating remains a major limitation to photovoltaic (PV) efficiency in high-temperature environments because excessive surface heat reduces electrical conversion and accelerates material degradation. This study integrates bibliometric and experimental approaches to develop a novel phase change composite (PCM) by combining paraffin with green composite materials (GCMs) derived from agricultural waste (pomegranate peel, sumac, and starch). Five PV panels with different PCM/GCM mixtures were tested under identical conditions to identify the most effective formulation. The optimal composition (57% paraffin and 43% pomegranate peel) achieved a melting point of 72°C and thermal conductivity of 0.1617 W/m.K, resulting in a 16.65% increase in daily energy output (240.98 Wh). Infrared imaging confirmed uniform temperature distribution and elimination of hot spots. The optimal condition was achieved because the fibrous pomegranate structure increased the melting point and stabilized the paraffin matrix, creating a porous network that improved heat absorption and distribution. This enhanced thermal regulation reduced surface temperature and hot spots, resulting in higher PV efficiency and energy output. This sustainable and low-cost innovation supports sustainable development goals (SDGs).